Проблеми формування культури споживання продукції пиво-безалкогольної промисловості - Страшинська, Лариса Володимирівна (My University, 2023)
Розглянуто проблеми формування культури споживання та принципи відповідального вживання пива. Узагальнено основні аспекти пропаганди галузевої компанії «Укрпиво» щодо відповідального споживання алкогольних і слабоалкогольних напоїв. Акцентовано увагу на необхідності поінформованості споживачів щодо можливих ризиків вживання алкоголю. The problems of the formation of consumption culture and the principles of responsible beer consumption are considered. The main aspects of the propaganda of the branch company "Ukrpivo" regarding the responsible consumption of alcoholic and low-alcohol beverages are summarized. Attention is focused on the need to inform consumers about the possible risks of alcohol consumption.
Keywords: кафедра маркетингу; культура споживання; алкогольні напої; відповідальне споживання; соціальні ініціативи; consumption culture; alcoholic and low-alcohol drinks; responsible consumption; social initiatives